The Harper Collins dictionary of economics - C. Pass.; Lowes, Bryan; Davis, Leslie; Kronish, Sidney J. (New York, N.Y. : HarperPerennial, 1991)
Contains more than 1,700 entries which go far beyond basic definitions, providing in-depth explanations and examples
Keywords: Economics -- Dictionaries; Wirtschaft; Economics